Team rewards 20 real life lessons - Parker, Glenn M. 1938- (HRD Press, 2010)
Annotation
Includes bibliographical references (page 24). - Print version record
Keywords: Teams in the workplace -- Problems, exercises, etc; Performance awards -- Problems, exercises, etc; Équipes de travail; Problèmes et exercices; Primes de rendement; Problèmes et exercices; Performance awards; Teams in the workplace; Management; Business & Economics; Management Styles & Communication; Problems and exercises